Penerapan Model Pembelajaran Kooperatif untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa pada Materi Konsep Perpindahan Kalor Kelas 5 di SDN Muara Pagatan Ujung - Muhammad Lazuardi; Lagiono; Syahbudin (Program Studi PGSD STKIP PGRI Banjarmasin, 2022)
The results of interviews and observations on March 8, 2022, with a class 5 teacher at SDN Muara Pagatan Ujung, the learning process presented by the teacher is not appropriate with the competence in the material to be achieved and the learning media is incomplete. This has resulted in the low level of individual and classical completeness. One alternative that is expected to improve student learning outcomes on the concept of heat transfer is to use the cooperative learning model. is a learning process centered on students who interact with each other in groups to achieve learning objectives through a learning media that has been designed. So it is expected to improve student learning outcomes on the concept of heat transfer. The purpose of this study was to determine the increase in student learning outcomes, increase student activity, increase teacher activity and student responses to the learning process. This research is a classroom action research (CAR) designed in 2 cycles with 4 meetings. The subjects of this study were 5th grade students of SDN Muara Pagatan Ujung. Data collection techniques from student learning outcomes were obtained from pre-test and post-test, student activities and teacher activities were obtained from observations and student responses were obtained from questionnaires. The data obtained were analyzed descriptively. The results showed that learning outcomes increased and reached the limit of classical completeness, namely in the post-test cycle 1 meeting 2 with a percentage of 73% increasing in cycle 2 meeting 2 to 86%. Student activity cycle 1 meeting 2 obtained an average value of 80 increased in cycle 2 meeting 2 to 95 with very good criteria. Teacher activity cycle 1 meeting 2 obtained an average value of 84 increased in cycle 2 meeting 2 to 95 with very good criteria and student responses to the learning process reached a percentage of 91% with a very positive category.